2023
DOI: 10.1186/s13047-023-00623-1
|View full text |Cite
|
Sign up to set email alerts
|

Elastography in the assessment of the Achilles tendon: a systematic review of measurement properties

Abstract: Background Managing and rehabilitating Achilles tendinopathy can be difficult, and the results are often unsatisfactory. Currently, clinicians use ultrasonography to diagnose the condition and predict symptom development. However, relying on subjective qualitative findings using ultrasound images alone, which are heavily influenced by the operator, may make it difficult to identify changes within the tendon. New technologies, such as elastography, offer opportunities to quantitatively investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 83 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…Ultrasound M-mode and ultrasound elastography assessments could be essential tools for researching the Achilles tendon [ 30 , 31 , 32 ], KFP, retrocalcaneal bursa, and deep soleal fibres, providing additional imaging analyses. Previous research has revealed structural modifications in the Achilles complex and identified changes in patients with AT.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound M-mode and ultrasound elastography assessments could be essential tools for researching the Achilles tendon [ 30 , 31 , 32 ], KFP, retrocalcaneal bursa, and deep soleal fibres, providing additional imaging analyses. Previous research has revealed structural modifications in the Achilles complex and identified changes in patients with AT.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the evaluation of AT stiffness using ultrasound elastography has become a valuable method [ 14 ]. However, the disadvantages of ultrasound elastography include differences in device performance and high cost, which make it difficult to use in clinical settings [ 15 ].…”
Section: Introductionmentioning
confidence: 99%